2011
DOI: 10.1371/journal.pone.0017627
|View full text |Cite
|
Sign up to set email alerts
|

A Combined Nucleic Acid and Protein Analysis in Friedreich Ataxia: Implications for Diagnosis, Pathogenesis and Clinical Trial Design

Abstract: BackgroundFriedreich's ataxia (FRDA) is the most common hereditary ataxia among caucasians. The molecular defect in FRDA is the trinucleotide GAA expansion in the first intron of the FXN gene, which encodes frataxin. No studies have yet reported frataxin protein and mRNA levels in a large cohort of FRDA patients, carriers and controls.Methodology/Principal FindingsWe enrolled 24 patients with classic FRDA phenotype (cFA), 6 late onset FRDA (LOFA), all homozygous for GAA expansion, 5 pFA cases who harbored the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
65
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(75 citation statements)
references
References 26 publications
9
65
0
Order By: Relevance
“…Such spatial specificity may cause more damage to neurons involved in lower limb functioning and vision, but relatively milder impairment of the neuronal substrates of speech and upper limb function. In classical FRDA, frataxin levels are very low [1,9]. p.R165P compound heterozygotes had higher mean frataxin levels than GAA-TRE homozygotes in both the present study and previous analyses of two Italian siblings [9].…”
Section: Resultssupporting
confidence: 67%
See 2 more Smart Citations
“…Such spatial specificity may cause more damage to neurons involved in lower limb functioning and vision, but relatively milder impairment of the neuronal substrates of speech and upper limb function. In classical FRDA, frataxin levels are very low [1,9]. p.R165P compound heterozygotes had higher mean frataxin levels than GAA-TRE homozygotes in both the present study and previous analyses of two Italian siblings [9].…”
Section: Resultssupporting
confidence: 67%
“…In classical FRDA, frataxin levels are very low [1,9]. p.R165P compound heterozygotes had higher mean frataxin levels than GAA-TRE homozygotes in both the present study and previous analyses of two Italian siblings [9]. Their atypical disease phenotype may be related to altered function of mutated frataxin in these patients, combined with lower total frataxin expression.…”
Section: Resultssupporting
confidence: 53%
See 1 more Smart Citation
“…The expansion of the intronic GAA repeat beyond the pathologic threshold inhibits FXN expression, resulting in decreased levels of FXN protein. 3,4 The EFACTS cohort study found that the number of GAA repeats on the patients' shorter allele inversely correlated with age at onset, with a mean of 745 repeats in the earlyonset group, 500 repeats in the intermediateonset group and 234 repeats in the lateonset group. The EFACTS paper 2 confirms previous reports 5, 6 that disease severity is associated with the size of the GAA expansion.…”
mentioning
confidence: 99%
“…A desired theoretical drug would not only increase mRNA and protein levels of frataxin [13] but also modulate the downstream changes associated with it.…”
Section: Resultsmentioning
confidence: 99%